Sustainable Economic Empowerment for The Creation of Economic Sovereignty in The Karangdoro Village Community - Muhamad Annas; Nurul Inayah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2024)
AbstractThis    assistance     will   examine    empowerment strategies    carried   out    from   a  Sustainable Development  perspective. This   mentoring   uses  a case  study approach  with   the aim of  finding out in   depth and    comprehensively   the  empowerment strategies carried   out  by accompanying  lecturers from      KH      Muhktar     Syafa'at     Blokagung Banyuwangi  University. The  data   sources  used in this assistance are from related parties as  well as secondary    data  sourced     from   documents  and field   observations.   This  assistance found  that empowerment  strategies    include    enabling    or facilitation   strategies  with  the  scope of group discussion  activities  and  the   construction   of empowerment   facilities    to   generate  community motivation,    strengthening    strategies   through activities   that focus    on  increasing  community capabilities  such  as   training in   forest coffee processing  and forest   bee cultivation, protection strategies regarding businesses. efforts  to form  a network  of forest   coffee  farmers   and marketing strategies    for   community    non-timber   forest products   as  well    as    support  strategies  by participating  in  technical activities  carried out with the abilities possessed such as financial audit and  negotiation  skills  with the  Perhutani Forest community.   The  impact     resulting   from   this empowerment     includes      three    aspects    of sustainable   development,      namely    ecological sustainability   marked  by   an    increase in  the number   of fauna    found in the   Perhutani Forest every  year, economic  sustainability created by the growth  of the community's    economic sector  other than   farming  and    the    growth   of  community initiatives  in   preserving  the  Perhutani  Forest which  is  a characteristic    of its  birth. social sustainability.